Graph models of automobile gears - kinematics - Drewniak, Józef; Kopeć, Jerzy; Zawiślak, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, kinematical analysis of an automotive gear is described. Versatile graph based methods have been utilized for this purpose. An application of mixed, contour and bond graphs gives the same results. It allows the detection of possible mistakes as well as a deeper insight into the designed artifact. The graphs can also be used for further analyses which will be published in a separate document.
Keywords: kinematical analysis; ratios; mixed graphs; contour graphs; bond graphs